The concept of self-regulation from the perspective of the qur'an: a thematic analysis for the development of contemporary educational counseling models - Muhammad Taufiq; Achmad Ruslan Afendi; Fadllurrohman Fadllurrohman; Ahmad Faqihudin; Moch Aminudin Hadi (Jurnal Konseling dan Pendidikan, 2026)
This study addresses the problem of weakened self-regulation among students in contemporary educational settings, particularly the lack of integration between psychological frameworks and spiritual values. The research aims to analyze the concept of self-regulation from the Qur’anic perspective and develop a thematic foundation for contemporary educational counseling models. This study employs a library-based qualitative approach, utilizing primary data from Qur’anic verses and secondary data from relevant books, journals, and previous research. Data were collected through systematic literature review and analyzed using content analysis to identify key themes. The findings reveal that Qur’anic self-regulation encompasses dimensions such as self-awareness, self-control, intention, accountability, and consistency. The study concludes that integrating these principles into educational counseling models can enhance students’ behavioral regulation, moral development, and overall effectiveness of counseling practices in a holistic and contextually relevant manner.